The 3‐nitro‐2‐pyridinesulfenyl group: synthesis and applications to peptide chemistry. (25th January 2017) - Rentier, Cédric; Fukumoto, Kentarou; Taguchi, Akihiro; Hayashi, Yoshio
Abstract : The 3‐nitro‐2‐pyridinesulfenyl chloride, commonly abbreviated as Npys‐Cl, was among the first stable heterocyclic sulfenyl halides to be isolated. After its discovery, the Npys group was widely used as a protecting group for the amines, alcohols and thiols. Herein, we have reviewed some of the aspects of the Npys‐Cl moiety, and its most promising recent uses are summarized, from the stability of the Npys protection of amines, hydroxyls and thiols and removal conditions for potential applications in peptide synthesis, to one of its most successful applications for the formation of mixed disulfides. Indeed, Npys protects thiols and acts as an activator for disulfide bond formation, thereby facilitating thiol/disulfide exchange to the corresponding disulfides. The selectivity and mild reaction conditions opened up a wide range of applications in chemical biology as well. Finally, some of the most recent developments regarding the synthesis and applications of solid‐phase Npys derivatives are discussed. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd. Abstract : The 3‐nitro‐2‐pyridinesulfenyl chloride was among the first stable heterocyclic sulfenyl halides to be isolated. It was discovered and widely used for protecting amines, alcohols and thiols as 3‐nitro‐2‐pyridinesulfenyl (Npys) derivatives. Herein are reviewed some of the aspects of the Npys‐Cl moiety, among which its stability as well as of the Npys protection/deprotection conditions, applications in peptide synthesis, disulfide bond formation properties, biological chemistry applications and finally the synthesis and use of solid‐phase Npys derivatives.